Committing genocide Using Artificial Intelligence Techniques - Hamed , Al-Bashir (Journal of Legal Sciences, 2026)
Throughout history, the international community has been exposed to many fierce wars, which has increased interest in the provisions of human rights and international humanitarian law. This is in light of the political, economic and social changes the world is experiencing, and the significant increase in victims resulting from these wars, especially in our Arab region, which is witnessing a series of armed conflicts and disputes. The International Criminal Court is the primary mechanism for prosecuting perpetrators of extremely serious crimes against the international order. The Court complements national criminal jurisdictions, and its jurisdiction and modus operandi are subject to the provisions of the Rome Statute of 1998. This represents the culmination of years of effort and the determination of the international community to ensure that those who commit serious crimes do not escape punishment. Genocide is one of the most serious international crimes, and one that raises the concern of the international community due to its dire consequences and catastrophic effects. This crime has caused enormous human losses when it invaded vast areas of the world, especially in the current century, which is described as the century of genocide. The crime of genocide has shocked the conscience of humanity, the essence of the global public order, and human dignity at its core, as a result of the horror of the heinous crime and the enormity of its abhorrent acts, which have been recorded in black ink in the annals of history. The tendency toward tyranny, domination, and arrogance has led brutal criminals to oppress and deprive the honorable and weak of their right to life. They have mercilessly and relentlessly exterminated entire sects and groups of people, despite the fact that these victims had not committed any crime or sin other than belonging to an ethnic, racial, or religious group. The bloody events currently taking place in the occupied Palestinian territories following October 7, which have resulted in thousands of Palestinian deaths and injuries, most of whom are women and children, is clear evidence of this. With the advancement of technology and the penetration of computers into all fields, artificial intelligence has become an integral part of it, with expectations of a significant dominance in the coming period, despite the many negative ethical implications of the increasing reliance on such technology, whether security, economic, or social. Hence, the need to establish legal rules commensurate with the nature of this technology, which is expected to prevail worldwide. In this context, military industries have been influenced by the gains in knowledge and technology, the resulting developments, the search for the best military means, and the reliance of modern weapons on technology and contemporary knowledge to perform their tasks. Electronics are employed for precise guidance, command, and control, and systems supported by artificial intelligence continuously monitor networks, detect electronic attacks, and respond to them quickly through autonomous systems capable of carrying out surveillance and reconnaissance missions. Therefore, it can be said that the development of artificial intelligence systems is significantly impacting various security and military sectors, whether in forecasting, reconnaissance and surveillance operations, or even weapons and combat and military tools. Wars and military battles are closer than ever to the stage of lethal algorithms, those autonomous weapons that rely on artificial intelligence technologies, such as robots, tanks, submarines, and combat drones that are programmed independently to interact, engage, and kill during military battles, without human intervention. These include semi-autonomous unmanned vehicles that are remotely controlled by a joystick, as if war were a video game. Therefore, the development and adoption of artificial intelligence by armies and armed movements represents a radical shift in the nature of conflict and competition, paving the way for a new era of warfare characterized by unprecedented capabilities.